Phenolic profiling and evaluation of in vitro antioxidant, α-glucosidase and α-amylase inhibitory activities of Lepisanthes fruticosa (Roxb) Leenh fruit extracts - Hasan Salahuddin, Mirfat Ahmad; Ismail, Amin; Kassim, Nur Kartinee; Hamid, Muhajir; Mat Ali, Mohd Shukri (Elsevier BV, 2020)
The present study focused on the phytochemical profiling along with evaluation of in vitro antioxidant, α-glucosidase and α-amylase inhibitory activities of various crudes and fractions obtained from Lepisanthes fruticosa (Roxb) Leenh fruit. Ethanolic seed crude extract exhibited the strongest radical scavenging, β-carotene bleaching activity, α-glucosidase inhibition and the highest total phenolic content (TPC). Column chromatography afforded various fractions with fraction M4 being the most potent due to the strongest radical scavenging, β-carotene bleaching, α-glucosidase inhibition and greatest amount of TPC. Liquid chromatography-tandem mass spectrometry (LC-MS/MS) analysis of ethanolic seed crude extract and fraction M4 showed the presence of various phytochemicals with antioxidant and antidiabetic properties, which include mostly flavonoids and tannins. The results may suggest that the ethanolic crude seed extract and its fraction could be an excellent source of bioactive phytochemicals with antioxidant and antidiabetic potential.